(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
Low oil recovery is one of the common problems in the field development of thin oil rims associated with gas-condensate. The fast gas and water conning of the reservoirs are the main causes of sharp oil rate decline and low cumulative oil production per well. Low recovery efficiency is related to the oil saturated thickness and if oil saturation is less than 10 m, most of oil volumes in place are moved to transition zones. 3D numerical and streamline simulations are performed for the development of thin oil rims of one of the pay zones in Bokabil Formation of Haripur gas field. The development option with four vertical oil production wells and nine water injection wells has been proposed to cover the entire reservoir with the efficient sweeping. The simulation study of the dynamic model has revealed that vertical wells through the reservoir are able to make a short drainage path and produce insignificant quantity of oil and the production period is terminated shortly. As an alternative development option a rim shaped production well and a rim shaped water injection well is designed. The development option with a rim shaped production and an injection wells covers large drainage length and produce significant amount of oil. This option is technically and economically feasible. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 85-88